Selected Approaches to Development of Employees as A Supporting Tool of Company Development in Era of Digitalization - Zuzana STOFKOVA (Communications of International Proceedings, 2021)
The article deals with the analysis of human resources development in selected company in Slovakia. HR development is not only an activity that improves the work performance of the company's employees as a whole, but also those that will bring personal growth to individuals. The main goal of this paper is to analyze and describe human resource development and education process. The article shows how the principles are applied in a selected company in automotive industry Slovakia. Data were collected through a questionnaire survey with employees in the selected company. Secondary data from corporate sources were also used. The aim of the research was to point out the impact of human resources development in a selected company and to find out the perception of the impact of employees development on their performance and to propose effective approaches to personnel development in a selected company with an impact on employees´ performance. The other goal of the research was to find out whether there was a dependence between the perceived performance of the employees and completion of technical training programs, as well as if the assumptions regarding the effectiveness of development of employees were confirmed. The hypothesis if the technical educational and trainee program lead to improvement of the performance of the employees was not confirmed.
Keywords: Human Resource Development; Education; Digitalization; Employees; Educational Programs